Votes that count and voters who don't : how journalists sideline electoral participation (without even knowing it) - Jarvis, Sharon E., 1969-; Han, Soo-Hye, 1976- (Rhetoric and democratic deliberation., 2018)
"Examines how journalists have portrayed electoral participation in the United States. The authors analyze depictions of voters in print news coverage over the course of eighteen presidential elections (1948-2016), describe people's reactions to those depictions, and share insights from their interviews with more than fifty elite journalists"--Provided by publisher